Induction Chemotherapy Plus Simultaneous Modulated Accelerated Radiation Therapy in Non-operative Hypopharyngeal and Supraglottic Laryngeal Squamous Cell Carcinoma: Long-Term Outcome of a Prospective Phase 2 Study - Cai, Boning; Meng, Lingling; Mo, Jingzi; Xu, Shouping; Qu, Baolin; Liu, Fang; Ma, Lin (Frontiers in Oncology, 2021)
BACKGROUND: To evaluate the toxicities and long-term outcomes of induction chemotherapy (ICT) plus simultaneous modulated accelerated radiotherapy (SMART) in nonoperative hypopharyngeal and supraglottic laryngeal squamous cell carcinoma (SCCH/L). MATERIAL AND METHODS: This was a prospective phase 2 study. Patients diagnosed with SCCH/L, aged from 18 to 75, staged from III to IVB in accordance with the AJCC 2010 criteria and refusing surgery, were eligible. The patients were treated with 2-3 cycles of docetaxel-cisplatin-based ICT, and SMART combined with 2-3 cycles of cisplatin-based concurrent chemotherapy. The prescription dose to the primary tumor and metastatic nodes was 69 Gy in 30 fractions. Acute and late toxicities were assessed according to the established RTOG/EORTC criteria and long-term outcomes were analyzed. RESULTS: Between February 2013 and June 2015, 55 newly diagnosed SCCH/L patients were enrolled. No grade 2 or worse acute xerostomia was noted. The incidences of grade 3 acute dermatitis, oral mucositis and pharyngoesophagitis were 12.7%, 3.6% and 12.7%, respectively. The median follow-up time was 48.0 months (range 5.5 to 74 months). The main late toxicity was hoarseness or sore throat, with an incidence of 32.7%. The 5-year functional larynx-preservation survival was 51.5%. The 3- and 5-year locoregional control and overall survival was 58.2% and 51.5%, 63.6% and 54.1%, respectively. CONCLUSIONS: ICT plus SMART with a regimen of 69 Gy/30 F for the treatment of SCCH/L demonstrated acceptable severe toxicity, satisfactory long-term outcomes and laryngeal function preservation.